Design of a Smart Village Management Information System Using Hybrid UML Modelling and COSMIC Approach - Susilo, Mochammad Zaki Cayvan; Dhenabayu, Riska; Dewi, Renny Sari; Ula, Ahmad Dicka Fajril (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
The Smart Village concept aims to improve public services, transparency, and citizen participation in rural areas. However, many Indonesian villages still rely on manual administrative processes, leading to inefficiencies and data inaccuracy. This study designs a Smart Village Management Information System (SVMIS) using the Unified Modeling Language (UML), focusing on use case and sequence diagrams to model system behavior. Functional size was measured using the COSMIC FSM method, yielding 59 COSMIC Function Points (CFP) across 16 transactional use cases. With a cost of IDR155,000 per CFP, the estimated development cost is IDR25,937,500—placing it in the medium complexity category based on the COSMIC sizing guide. The system includes five key modules: user management, correspondence, notifications, social assistance, and multi-role access control. This modular design supports efficiency, transparency, and aligns with global smart village initiatives focused on digital infrastructure and data-driven governance.